2017
DOI: 10.1101/221986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevention and reversion of pancreatic tumorigenesis through a differentiation-based mechanism

Abstract: SUMMARYActivating mutations in Kras are nearly ubiquitous in human pancreatic cancer and initiate precancerous pancreatic intraepithelial neoplasia (PanINs) when induced in adult murine acinar cells. PanINs normally take months to form, but can be rapidly induced by genetic deletion of acinar cell differentiation factors such as Ptf1a, suggesting that loss of mature cell identity is a rate-limiting step in pancreatic tumor initiation. Using a novel genetic mouse model that allows for independent control of onc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Moreover, reexpression of Ptf1a in PDAC precursor lesions reverts their status to fully differentiated exocrine cells. [78][79][80] Similar observations have been published for other acinar cell transcription factors, Mist-1, 81 Nr5a2, 82 and Gata6. 83 In conclusion, while studies using human tissue are lacking, there is vast evidence for mouse acinar cell derived PDAC formation.…”
Section: Neoplastic Transformation a Whodunitsupporting
confidence: 85%
“…Moreover, reexpression of Ptf1a in PDAC precursor lesions reverts their status to fully differentiated exocrine cells. [78][79][80] Similar observations have been published for other acinar cell transcription factors, Mist-1, 81 Nr5a2, 82 and Gata6. 83 In conclusion, while studies using human tissue are lacking, there is vast evidence for mouse acinar cell derived PDAC formation.…”
Section: Neoplastic Transformation a Whodunitsupporting
confidence: 85%
“…Both of these TFs are frequently downregulated during neoplastic development and malignant progression of human and mouse PDAC. Functional genetic studies in mice and cultured human PDAC cells have demonstrated that experimentally forced expression of PTF1a impairs KRAS-induced transdifferentiation and proliferation, and can also force the redifferentiation of already neoplastic cells into a quiescent acinar cell phenotype (26). Conversely, suppression of PTF1a expression elicits acinar-to-ductal metaplasia, namely transdifferentiation, and thereby sensitizes the duct-like cells to oncogenic KRAS transformation, accelerating subsequent development of invasive PDAC (27).…”
Section: Transdifferentiationmentioning
confidence: 99%
“…To date, several pathways and transcription factors implicated in the differentiation state of carcinoma have been revealed; albeit, these components have been identi ed as those that mostly orchestrate metabolism and the epigenome [18][19][20][21] . Since these mechanisms are mostly conserved, therapeutic strategies towards such targets are less likely to be circumvented by cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant with the functional studies of phenotypic plasticity within the last decade, several transcription factors have been identi ed as regulators of the differentiation state of carcinoma cells; albeit, these targets are currently undruggable [18][19][20][21] . Thus, we urgently need to identify actionable therapeutic targets to revert de-differentiation of carcinoma cells and to re-sensitize them to existing therapies.…”
Section: Introductionmentioning
confidence: 99%